Lexical Units of Lemky Dialect in the Folklore Records of Orest Hyzha (Linguostylistic Studies, 2019)
The riches of the Ukrainian dialectal lexicon provide multifaceted opportunities for the study of its composition structure, the system of organization, features of functioning and its areal specifics. One of the most important tasks of modern Ukrainian dialectology is the systemic study of the vocabulary throughout the ethnic-speaking territory. In this context, the study of the dialects that have lost the integrity of areal as a result of political processes becomes a topical scientific issue. In the middle of the twentieth century (1944–1947), the Western ethnic group of the Ukrainians, Lemki, experienced the greatest tragedy in history – forced eviction from their native lands to the territory of the Ukrainian SSR and the north-western lands of Poland. In 1945 a doctor-dentist, musician-amateur, a well-known collector of Lemky folk songs Orest Hyzha was deported to Ukraine. His collection «Ukrainian Folk Songs from Lemkivshchyna» includes 300 song samples, recorded by O. Hyzha since1933.The article analyzes the dialectal lexical units revealed in the folk texts of Lemky-migrants. The materials of the case study allowed to distinguish ten lexical-semantic groups: 1) verbs (words for the designation of physiological, mental processes and states, verbs of motion and displacement, actions that cause changes in the object, speech processes); 2) lexicon to indicate the names of buildings, agricultural structures, their parts and other related objects; 3) vocabulary for designating persons by the kind of their activity or employment; 4) vocabulary for the designation of family members, families, family ties, the names of persons by their matrimonial or age status; 5) adjectives with the positive / negative connotation; 6) the names of the garments and footwear; 7) the names of foods, drinks, kitchen utensils; 8) the names of the household objects; 9) vocabulary for designation of the realities of the animal-plant world (flora and fauna); 10) appellative names for the geographical concepts. In the lyrics, there are also a lot of borrowings from other languages, especially from the neighboring countries (Polish, Slovak and German). The register of dialectical vocabulary reflects the local characteristic features of the carriers of the southern-western Lemky dialect. The dialectal core of the folk songs language of the south-west dialect proves the necessity of involving multi-ethnic folklore texts into the dialectological research. Key words: dialectical vocabulary, folklore, Lemki, the dialect of Lemki, Southwestern dialect, nomen, lexical-semantic group. SourcesEtymolohichnyi slovnyk ukrainskoi movy, edited by O. S. Melnychuk. 7 vols. Kyiv: Naukova dumka, 1982–2012.Slovnyk ukrainskoi movy, edited by I. K. Bilodid. 11 vols. Kyiv: Naukova dumka, 1970–1980.Ukrainski narodni pisni z Lemkivshchyny. Horlytsi, 1997–2002. ReferencesVerkhratskyi, Ivan. Pro hovor halytskykh Lemkiv. Lviv, 1902.Zhylko, Fedot. Hovory ukrainskoi movy. Kyiv, 1958.Zaleskyi, Anton. “Naibilsh zakhidnyi ukrainskyi hovir”. Kultura slova, iss. 33, 1987, pp. 68–71.Nakonechny, Volodymyr. Lemki in the XX century: life on the ethnic lands and the new geopolitical context. PhD Thesis Abstract. Kyiv, 2008.Orlowska B.-A. “Assimilation or adaptation of Lemkos in the western Polish”. Karpatskyi kray. no 1 (3), 2013, pp. 5–12.Pyrtei, P. Korotkyi slovnyk lemkivskykh hovirok. Ivano-Frankivsk: Siversiia MV, 2004.Uhoda mizh Uriadom Ukrainskoi Radianskoi Sotsialistychnoi Respubliky i Polskym Komitetom Natsionalnoho vyzvolennia pro evakuatsiiu ukrainskoho naselennia z terytorii Polshchi i polskykh hromadian z terytorii URSR (vid 09.09.1944). zakon3.rada.gov.ua/laws/show/616_065Ukrainskyi instytut natsionalnoi pamiati. www.memory.gov.uaKhaliuk, Lesia. “The 1947 Operation Vistula in the Light of Oral Narratives of Ukrainian Settlers: A History of Studies and Themes”. Folk art and ethnology, no 3, 2018, pp. 71–8.Studia methodologica, iss. 27, 2009.Z łemkowskiej skrzyni. W 2 cz. Lemko-Tower, 2004.